2019
DOI: 10.3389/fneur.2019.00868
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Oligodendrocyte Glycoprotein (MOG) Antibody Diseases in Children in Central South China: Clinical Features, Treatments, Influencing Factors, and Outcomes

Abstract: Background and purpose: The clinical and radiological features of myelin oligodendrocyte glycoprotein antibody (MOG-Ab) diseases vary among the patients and studies. In addition, the clinical significance of MOG-Ab for the diagnosis, treatment, and prognosis is not yet established. Therefore, we aimed to evaluate the clinical, radiological, treatments and outcome features of MOG-Ab diseases in Central Southern part of China. Methods: A retrospective study of children with MOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 31 publications
(37 reference statements)
4
34
0
Order By: Relevance
“…To date, no nationwide study has been conducted regarding the incidence of MOGAD in China. A recent study ( 16 ), which included 25 Chinese pediatric MOGAD patients, revealed that Chinese children and Caucasians share the same clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no nationwide study has been conducted regarding the incidence of MOGAD in China. A recent study ( 16 ), which included 25 Chinese pediatric MOGAD patients, revealed that Chinese children and Caucasians share the same clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…100 A decrease in the ARR while on rituximab has been documented in 9 patients from this study 26 and in 9 of 10 children from a Chinese study on relapsing MOGAD. 99 The occurrence of relapses despite B-cell depletion was observed in 1 of 6 children from an Australasian study. 89 The biological effect of rituximab through the monitoring of lymphocyte subsets (CD19+ and CD27+ B-cells) has been evaluated recently.…”
Section: Rituximabmentioning
confidence: 96%
“…98 Data on the use of rituximab in relapsing MOG demyelination from small retrospective pediatric studies suggest some effectiveness in relapse prevention, although documented benefit is lower than expected. 26,89,[99][100][101] In 12 children with a relapsing MOGAD (ADEM, ON, NMOSD), no clinical relapses or new MRI lesions were observed during the first year of rituximab treatment. 100 A decrease in the ARR while on rituximab has been documented in 9 patients from this study 26 and in 9 of 10 children from a Chinese study on relapsing MOGAD.…”
Section: Rituximabmentioning
confidence: 99%
“…In addition, the deep gray matter can also been frequently affected. Mao L et al, retrospective reviewed 50 Chinese cases with MOG-EM, and the 29% of whom had the deep gray matter involvement, including thalamus and basal ganglia [ 4 ]. However, the symmetrical basal ganglia and thalamus involvement is rarely reported.…”
Section: Discussionmentioning
confidence: 99%